Dynamic simulation of FWD tests on flexible transversely isotropic pavements with imperfect interfaces. (February 2021) - Han, Zejun; Zhang, Jin; Xue, Luanluan; Fang, Hongyuan; Xiao, Ziwei
Abstract: Developing an accurate and efficient forward model of the dynamic response of pavement structure is of great significance for obtaining the design parameters of the layered pavement structure through an inverse calculation based on the measured pavement data. However, the existing algorithms rarely consider the interlayer contact. Based on the traditional spectral element method (SEM), this study proposes a new forward model to simulate the falling weight deflectometer (FWD) dynamic tests for the transversely isotropic layered pavement structure. The interfaces between the pavement layers can be imperfect, and the displacement boundary conditions are discontinuous. Moreover, the developed model considerably enhances the efficiency of the model in solving the dynamic response of transversely isotropic layered media by avoiding the infinite integration in integral transformation. Numerical examples verify the accuracy and efficiency of the model developed in this study. At the same time, an extensive parameter analysis is conducted on the interlayer contact of the pavement structure and inhomogeneity of the layered soil, which provides a reliable, numerical, theoretical basis for the design of pavement structure.